Implicit statistical learning of patterns in orthography to phonology mappings in Chinese EFL learners - Ling, K (2022)
This study attempted to provide deeper insight into how adult EFL learners with a fundamentally different language system, that is, Mandarin Chinese, learn the English orthography-to-phonology patterns under brief incidental exposure. This quantitative research used pre- and post-test design to test the learning of the real English spelling patterns, i.e., the spelling and pronunciation patterns of letter <c>, in the experimental and control conditions. With Mandarin Chinese as their native languages, it may be possible that Chinese EFL learners' L1 may affect their learning of English spelling and pronunciation patterns. Therefore, the researcher is also interested in examining whether learners with better Chinese and English phonemic awareness may perform and improve better in the mapping task. In this sense, the researcher explored the correlations between Chinese and English phonological systems and their performance in orthography-phonology mapping.